AN ABSTRACT MOVE ANALYSIS IN NATIONAL JOURNALS: A CASE STUDY ON SPORTS SCIENCE RESEARCH ARTICLES - Annisa Roffina Nurprili, - (2023)
Abstract is one of the essential parts of a research article which has a significant role in attracting the reader's attention. Although abstract has received much attention in the literature, only a few have explored the rhetorical move and linguistic features realization in the abstracts of sports science research articles by also taking into account different Sinta levels. This study aims to: 1) explore the rhetorical moves and investigate the linguistic features used in the abstracts of sports science research articles published on different Sinta (Science and Technology Index) levels, 2) find out whether Sinta levels influence the realization of moves and steps in the abstracts. The study used the five models theory by Hyland (2000) as the framework and involved 120 abstracts; 24 research articles' abstracts from each level of Sinta were selected within the publication range of 2015-2022. The findings of this study show that although differences in terms of moves, steps, and linguistic features realization across the Sinta level emerged, the differences are not substantial. It can be concluded that the Sinta level is not likely to fully influence the differences and similarities in using moves, steps, and linguistic features in sports science research articles' abstracts.